Association of endocrine disrupting chemicals exposure with human chorionic gonadotropin concentrations in pregnancy - Arash Derakhshan; Huan Shu; Maarten A.C. Broeren; Andreas Kortenkamp; Christian H. Lindh; Barbara Demeneix; Robin P. Peeters; Carl-Gustaf Bornehag; Tim I.M. Korevaar (Environment International, 2023)
Background: Human chorionic gonadotropin (hCG) is produced by the placenta and plays an essential role in the maintenance of pregnancy. Endocrine disrupting chemicals (EDCs) have the potential to interfere with functions related to the production and secretion of hCG; however associations between exposure to EDCs and hCG concentrations in humans remain to be elucidated. Objectives: To investigate the association of urinary, serum and plasma concentrations of EDCs during pregnancy with serum hCG concentrations. Methods: We utilized data form the Swedish Environmental Longitudinal, Mother and child, Asthma and allergy (SELMA) study. We investigated the association of 26 EDCs measured in early pregnancy urine or blood with serum hCG concentrations using multi-variable adjusted linear regression models per EDC and Weighted Quantile Sum (WQS) regression with repeated holdout validation for the EDCs mixture. Results: In 2,039 included women, higher exposure to bisphenol A was associated with lower hCG (beta [95% CI]: −0.06 [−0.11 to −0.002]) while higher triclosan exposure was associated with a higher hCG (0.02 [0.003 to 0.04]). Higher exposure to several phthalates, including mono-ethyl and mono-butyl phthalates (MEP and MBP) as well as metabolites of di-2-ethylhexyl phthalate (DEHP) was associated with a lower hCG (beta [95% CI] for sum of DEHP metabolites: −0.13 [−0.19 to −0.07]). Likewise, higher exposure to several polychlorinated biphenyls (PCBs) was associated with a lower hCG. In the WQS regression, each quartile increase in the EDCs mixture was associated with −0.27 lower hCG (95% CI: −0.34 to −0.19). Discussion: Higher exposure to several EDCs during pregnancy was associated with a lower hCG; and despite the small effect sizes, still indicating that the exposure may negatively affect production or secretion of hCG by the placenta. Our results provide the impetus for future experimental studies to investigate the placenta as a target organ for adverse effects of EDCs.